Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the inverse of the function
[tex]\[ y = x^2 + 4x + 4 \][/tex]
we need to express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
### Step-by-Step Solution
1. Rewrite the original function:
The given function is
[tex]\[ y = x^2 + 4x + 4 \][/tex]
2. Express the quadratic function in standard form:
Notice that the quadratic function [tex]\( x^2 + 4x + 4 \)[/tex] can be written as a perfect square:
[tex]\[ x^2 + 4x + 4 = (x + 2)^2 \][/tex]
So, the function becomes:
[tex]\[ y = (x + 2)^2 \][/tex]
3. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
To find the inverse, we need to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = (x + 2)^2 \][/tex]
Take the square root of both sides to solve for [tex]\( x + 2 \)[/tex]:
[tex]\[ \sqrt{y} = x + 2 \][/tex]
or
[tex]\[ -\sqrt{y} = x + 2 \][/tex]
4. Isolate [tex]\( x \)[/tex]:
Solving for [tex]\( x \)[/tex], we get two solutions:
[tex]\[ x = \sqrt{y} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y} - 2 \][/tex]
Thus, the function [tex]\( y = x^2 + 4x + 4 \)[/tex] has two inverse functions:
[tex]\[ x = \sqrt{y} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y} - 2 \][/tex]
So the inverse functions are:
[tex]\[ f^{-1}(y) = \sqrt{y} - 2 \][/tex]
and
[tex]\[ f^{-1}(y) = -\sqrt{y} - 2 \][/tex]
Finally, these can also be rewritten as:
[tex]\[ x = \sqrt{y - 2} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y - 2} - 2 \][/tex]
So, the inverse functions are:
[tex]\[ f^{-1}(y) = \sqrt{y - 2} - 2 \][/tex]
and
[tex]\[ f^{-1}(y) = -\sqrt{y - 2} - 2 \][/tex]
These results indicate two possible inverse functions, capturing the symmetrical nature of quadratic equations.
[tex]\[ y = x^2 + 4x + 4 \][/tex]
we need to express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
### Step-by-Step Solution
1. Rewrite the original function:
The given function is
[tex]\[ y = x^2 + 4x + 4 \][/tex]
2. Express the quadratic function in standard form:
Notice that the quadratic function [tex]\( x^2 + 4x + 4 \)[/tex] can be written as a perfect square:
[tex]\[ x^2 + 4x + 4 = (x + 2)^2 \][/tex]
So, the function becomes:
[tex]\[ y = (x + 2)^2 \][/tex]
3. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
To find the inverse, we need to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = (x + 2)^2 \][/tex]
Take the square root of both sides to solve for [tex]\( x + 2 \)[/tex]:
[tex]\[ \sqrt{y} = x + 2 \][/tex]
or
[tex]\[ -\sqrt{y} = x + 2 \][/tex]
4. Isolate [tex]\( x \)[/tex]:
Solving for [tex]\( x \)[/tex], we get two solutions:
[tex]\[ x = \sqrt{y} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y} - 2 \][/tex]
Thus, the function [tex]\( y = x^2 + 4x + 4 \)[/tex] has two inverse functions:
[tex]\[ x = \sqrt{y} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y} - 2 \][/tex]
So the inverse functions are:
[tex]\[ f^{-1}(y) = \sqrt{y} - 2 \][/tex]
and
[tex]\[ f^{-1}(y) = -\sqrt{y} - 2 \][/tex]
Finally, these can also be rewritten as:
[tex]\[ x = \sqrt{y - 2} - 2 \][/tex]
and
[tex]\[ x = -\sqrt{y - 2} - 2 \][/tex]
So, the inverse functions are:
[tex]\[ f^{-1}(y) = \sqrt{y - 2} - 2 \][/tex]
and
[tex]\[ f^{-1}(y) = -\sqrt{y - 2} - 2 \][/tex]
These results indicate two possible inverse functions, capturing the symmetrical nature of quadratic equations.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.